2009
DOI: 10.1039/b820493d
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative analysis of metal alloys, brass and soil samples by calibration-free laser-induced breakdown spectroscopy: recent results and considerations

Abstract: The calibration-free methodology described in the literature dealing with the technique of laser induced breakdown spectroscopy has been applied here to several samples under different operating pressures with the aim of classifying the analytical technique as quantitative, semi-quantitative or qualitative (with quantitative estimates only), depending on the relative percentage errors calculated for the major, minor and trace elemental composition of the sample. The results were obtained with a Q-switched Nd:Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 60 publications
(86 reference statements)
2
46
0
Order By: Relevance
“…Thiyagarajana and Scharer 17 have shown that the plasma of air is in LTE condition for time less than 2 microseconds. The same conclusion has been found by Herrera et al 18 by studying Al alloy laser induced plasma in air generated by Nd:YAG laser. Barthelemy et al 19 have studied the Al plasma by excimer laser in air, they found some evidence of a departure from LTE for the ionized states, presumably because the plasma cannot be considered stationary for the higher energy states.…”
Section: Introductionsupporting
confidence: 76%
“…Thiyagarajana and Scharer 17 have shown that the plasma of air is in LTE condition for time less than 2 microseconds. The same conclusion has been found by Herrera et al 18 by studying Al alloy laser induced plasma in air generated by Nd:YAG laser. Barthelemy et al 19 have studied the Al plasma by excimer laser in air, they found some evidence of a departure from LTE for the ionized states, presumably because the plasma cannot be considered stationary for the higher energy states.…”
Section: Introductionsupporting
confidence: 76%
“…It is clear that using an echelle-like instrument as the spectral resolving system allows saving measurement time, because a broadband spectrum is acquired in a single run. However, CF-LIBS analysis of wide range spectra collected by multiple acquisitions of successive spectral windows with a grating monochromator has been also documented with very good results [19]. The crucial points are: the accurate characterization of the instrument spectral efficiency over the whole wavelength range of interest and the stability of plasma (and instrumental) conditions during the measurement.…”
Section: Overview Of Cf-libs Applicationsmentioning
confidence: 97%
“…Most frequently, the CF-LIBS analysis has been applied to solid materials: aluminum alloys [7,[15][16][17][18][19], steel and iron alloys [15,[18][19][20], precious alloys for jewelry [21,22], copper alloys [19,[23][24][25][26][27][28], archaeological copper artifacts [24,29], glasses [23], pigments on roman frescoes [30] and on parchments [31], soils and rocks [32][33][34], meteorites [35], coral skeletons [36], human hair [37].…”
Section: Overview Of Cf-libs Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While matrix-matched calibration-curves can be used for quantitative analysis of solids (Hunter and Piper, 2006;Eppler et al, 1996), various groups have successfully implemented CF-LIBS to quantify the composition of metal alloys (Tognoni et al, 2007(Tognoni et al, , 2010Ciucci et al, 1999;Herrera et al, 2009a) and metal oxides (Praher et al, 2010) in a gaseous environment, achieving relative accuracies of 5 to 15% for major elements. With regard to interpretation of natural sediments and rocks, most studies report degradation in accuracy due to the complexity of the signals obtained (Tognoni et al, 2010;Herrera et al, 2009b;Colao et al, 2004;De Giacomo et al, 2007). Moreover, conventional CF methods require all the major elements to be identified in the spectra, which is not possible for the limited range and resolution of the spectrometer used in ChemiCam.…”
Section: Sediments and Rocksmentioning
confidence: 97%